A Quantitative Investigation of the Laffer Curve on the Continued Work Tax : The French Case - Jean-Olivier Hairault; François Langot; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2005)
It is often argued that the tax on continued work should be removed by implementing actuarially fair schemes. However, these schemes cannot help fund the expected Social Security deficit. This paper proposes to give individuals only a fraction of the marginal actuarially fair incentives in case of postponed retirement. Social Security then faces a tradeoff between giving enough incentives to make individuals actually delay retirement and giving little increase in pensions in order to help finance its expected deficit. This trade-off is captured by a Laffer curve that we quantify on French data. Furthermore, we analyze the interactions between wealth and retirement behavior.
Keywords: J26; H55; H31; 330; retirement behavior and wealth; actuarially fair benefits; Altersgrenze; Ältere Arbeitskräfte; Arbeitsangebot; Sozialversicherungsbeitrag; Laffer-Kurve; Rentenfinanzierung; impli; Frankreich